The D-lactate enigma: exploring the inflammatory influence of D-lactate in cattle - Burgos, Rafael Agustín; Manosalva, Carolina; Alarcón, Pablo; Navarro, Max; Quiroga, John; Morán, Gabriel; Gallastegui, Jan; Brauchi, Sebastián; Carretta, María Daniella (Frontiers in Veterinary Science, 2024)
D-lactic acidosis is associated with fermentative disturbances and is often marked by elevated levels of D-lactic acid in the blood, ruminal fluid, and synovial fluid in cattle. D-lactic acidosis is linked to various inflammatory manifestations, and although the causative factors have been extensively explored, the exact pathogenesis of the associated inflammation remains elusive. Notably, less attention has been given to D-lactate, a stereoisomer found in the plasma of affected animals, which may lead to D-lactic acidosis. This review aims to highlight the evidence suggesting that D-lactate participates in the modulation of inflammatory processes and explore its potential effects on synoviocytes, polymorphonuclear neutrophils, macrophages, and T-cells. This comprehensive examination of D-lactate’s involvement in the inflammatory response process provides timely insights into the pathophysiological aspects of ruminal acidosis in cattle.